Coronary Arteriovenous Fistula Causing Hydrops Fetalis - AKALIN, FİGEN (My University, 2014)
Fetal heart failure and hydrops fetalis may occur due to systemic arteriovenous fistula because of increased cardiac output. Arteriovenous fistula of the central nervous system, liver, bone or vascular tumors such as sacrococcygeal teratoma were previously reported to be causes of intrauterine heart failure. However, coronary arteriovenous fistula was not reported as a cause of fetal heart failure previously. It is a rare pathology comprising 0.2-0.4% of all congenital heart diseases even during postnatal life. Some may remain asymptomatic for many years and diagnosed by auscultation of a continuous murmur during a routine examination, while a larger fistulous coronary artery opening to a low pressure cardiac chamber may cause ischemia of the affected myocardial region due to steal phenomenon and may present with cardiomyopathy or congestive heart failure during childhood. We herein report a neonate with coronary arteriovenous fistula between the left main coronary artery and the right ventricular apex, who presented with hydrops fetalis during the third trimester of pregnancy.